2016
DOI: 10.1089/end.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Staff Radiation Protection During Fluoroscopy-Guided Urologic Interventions

Abstract: In the present study, radiation exposure for urologists was low, but so was knowledge of radiation safety and optimization practices. This absence of training for radiation safety and reduction, teamed with novel techniques involving long fluoroscopy-guided interventions, could result in unnecessarily high exposure for patients and OR personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 5 publications
1
7
0
3
Order By: Relevance
“…The French Association for Urology Residents in their prospective study found that 90% of their participants reported a lack of collective protective equipment in their operating rooms. 20 Our study yielded a similar result with the majority of our participants (80%) reporting a lack of availability of protective equipment such as lead aprons and thyroid shields. This may be attributed to an increased usage of fluoroscopy that has not been matched by procurement of sufficient safety and protective equipment.…”
Section: Discussionsupporting
confidence: 83%
“…The French Association for Urology Residents in their prospective study found that 90% of their participants reported a lack of collective protective equipment in their operating rooms. 20 Our study yielded a similar result with the majority of our participants (80%) reporting a lack of availability of protective equipment such as lead aprons and thyroid shields. This may be attributed to an increased usage of fluoroscopy that has not been matched by procurement of sufficient safety and protective equipment.…”
Section: Discussionsupporting
confidence: 83%
“…Over the last two decades, minimally invasive surgery for nephrolithiasis has gained in popularity [ 1 ]. Fluoroscopy is routinely used during these procedures and as a result radiation exposure for patients and medical staff increased consequently.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of fluoroscopic guided access (FGA) to the kidney is that there is no real time visualization of adjacent organs, such as the bowel, liver or pleural space, with increased risk of injury to these structures [13,14]. Also, this approach exposes the patient and the surgical staff to radiation, which is lower but significant for the surgeon [15][16][17] . The patient is exposed to a mean of 8.66 mSv [18] during a PCNL session, with a peak in the first step, when gaining access to the collecting system [19], the risk of irradiation being dose dependent [20].…”
Section: Introductionmentioning
confidence: 99%